PENGARUH IKLIM KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN DI PT TELKOM AKSES SAMARINDA - Fajar Ainun Muhammad nebong (ADMINISTRASI PUBLIK, 2019)
Organizational communication climate is the employee 's perception of the messages or events that occur in the company. Lack of attention and communication between leaders and subordinates that affect the performance of the background of the researcher wants to know about it, especially in PT Telkom Akses Samarinda. PT Telkom Akses Samarinda as a company must have good organizational communication climate . With good communication climate, PT Telkom Akses Samarinda employees can complete the task properly. Organizational communication climate change will affect the productivity or performance of an employee because of the size of the focus of the staff's performance in achieving corporate goals . In this study, researchers used the theory of human relations. This theory emphasizes the importance of individuals in the organization and social relationships in organizational life. The method used is a quantitative method that is associative. The purpose of this research is to know is there any effect of organizational communication climate on employee performance. Based on the results of the study conducted by researchers correlation analysis between the variables x and y indicate that the variable x has a positive significant relationship with the variable y, that is equal to 0,606, then in accordance with the guidelines of the correlation coefficient is a strong relationship category. SPSS 17.00 output results expressed that relationship between organizational communication climate to employee performance in PT Telkom Akses Samarinda have a strong relationship, and have the significant positive value. Based on the calculation of the value of t, it can be seen that the tvalue is 4,6. While a scale value ttable was 0.264. Rated 4.6 > 0.264, so it can be concluded that H 0 is rejected and H a is accepted. This means that there is a positive and significant relationship between organizational